Risk factors for oral health in young, urban, Aboriginal and Torres Strait Islander children - Butten, K; Johnson, NW; Hall, KK; Anderson, J; Toombs, M; King, N; O'Grady, KF (Australian dental journal, 2019)
Background The caries process follows a strong social gradient which can commence in the first years of life. Yet data on young children remain limited. This study reports the potential risk factors and indicators in urban, Aboriginal and Torres Strait Islander children aged less than 5 and estimates the prevalence of caries. Methods Demographic and risk factor and risk indicator data were collected at baseline in a cohort study of children attending a health clinic in north Brisbane. Dentulous children received a basic oral examination to explore the presence of decayed, missing and filled teeth (dmft). Descriptive analyses were performed. A backwards stepwise logistic regression model was performed to identify potential associations with dmft status. Results In this study, 180 children enrolled: 111 children received the oral examination, of whom 14 (12.6%) (mean age 35 months) were estimated to have dmft >0. There was a high prevalence of socio‐economic, dietary and behavioural risk factors/indicators present for children. Due to the small sample size, planned regression was not performed. Conclusions Overall, the prevalence of risk factors and risk indicators for caries in the study population is high. More culturally appropriate resources that support preventive care need to be invested before children are school aged.